Comparison of weekly HRV measures collected from two different recording times and their relation to performance in collegiate female rowers - Sherman, S. R.; Esco, M. R.; Fedewa, M. V.; MacDonald, H. V.; Freeborn, T. (Graduate School of The University of Alabama; Department of Kinesiology, 2018)
INTRODUCTION: Root-mean-square difference of successive RR intervals (RMSSD) is a common heart rate variability (HRV) metric used in the realm of athletic monitoring. Time constraints in a collegiate sport environment and irregular practice hours are challenges that make obtaining the mean value (RMSSDM) and coefficient of variation (RMSSDCV) of daily RMSSD assessment difficult. It is unclear whether the time of day (i.e., measured immediately upon waking versus immediately prior to morning practice) influences these metrics and their relationships to performance. PURPOSE: To compare HRV values when recorded immediately upon waking to values recorded later in the morning prior to practice, and to determine the associations of HRV measures with performance outcomes in competitive female rowers. METHODS: Thirty-one NCAA Division I rowers were monitored for six consecutive days. Two seated RMSSD measurements were obtained on at least three mornings using a photoplethysmography application. Each 1-minute RMSSD measure was recorded following a 1-minute stabilization period. The first (T1) measurement occurred at the athlete`s home following waking, the second (T2) upon arrival at the team`s boathouse immediately before practice. From the daily measures, RMSSD mean and CV were calculated. Rank was determined by the coaches based on performance for that week. Two objective performance assessments were conducted on an indoor rowing ergometer on separate days: timed 2000m and distance covered in 30 minutes. Paired samples t-test was used to assess the potential differences between T1 and T2. Bivariate correlations were assessed using an intraclass correlation coefficient (ICC). Statistical significance assessed using a-level, p<0.05. RESULTS: No differences in RMSSDM and RMSSDCV were observed between T1 and T2 (p=0.73, p=0.66, respectively). RMSSDM at T1 and T2 were strongly correlated (ICC=0.82, 95% CI=0.63 to 0.92), as well as RMSSDCV at both times (ICC=0.75, 95% CI=0.48 to 0.88) (both p<0.01). RMSSDM at T1 and T2 was moderately associated with athlete rank (r=-0.55, r=-0.46, respectively), 30-min distance (r=0.40, r=0.41, respectively), and 2,000m at T1 (r=-0.37). No significant correlations were observed for RMSSDCV. CONCLUSIONS: Ultra-short RMSSD can be measured immediately upon waking or prior to practice, however assessing HRV immediately upon waking yielded stronger correlations with performance.